Separate spheres no more : gender convergence in American literature, 1830-1930 - Elbert, Monika M. (Monika Maria), 1956- (University of Alabama Press, 2000)
Although they wrote in the same historical milieu as their male counterparts, women writers of the 19th- and early 20th-centuries have generally been ""ghettoized"" by critics into a separate canonical sphere. These original essays argue in favor of reconciling male and female writers, both historically and in the context of classroom teaching. While some of the essays pair up female and male authors who write in a similar style or with similar concerns, others address social issues shared by both men and women, including class tensions, economic problems, and the Ci